KEJADIAN STUNTING PADA BALITA 24-59: ANALISIS FAKTOR PENYEBAB - Idris, Idris; Zahrah, Nisri Ina; Fitria, Lia; Kartadarma, Supriyatni (Ensiklopedia of Journal, 2025)
Stunting in children is a condition that develops through a cumulative process and occurs over a long period of time, beginning during pregnancy, continuing into childhood, and continuing to have an impact throughout the life cycle. The purpose of this study was to analyze the factors causing stunting. The research design used in this study was cross-sectional. The research was conducted in Hutaraja Village in November 2024. The population consisted of all families with toddlers aged 24–59 months who were categorized as stunted. The sample consisted of 104 people. The sampling technique used purposive sampling. The research instrument used a research questionnaire. Data analysis was performed using univariate and bivariate methods. The results showed a relationship between a history of low birth weight (p value: 0.025) and exclusive breastfeeding (p value: 0.045) with stunting. It is recommended that community health centers increase the intensity of health education on stunting to the community, especially mothers of toddlers. Keywords: Infants, low birth weight, stunting